Prevalence and predictors of obesity-related cancers among racial/ethnic groups with metabolic syndrome. - Shanada Monestime; Bettina Beech; Dulcie Kermah; Keith Norris (PLoS ONE)
Background Obesity-related cancer (ORC) is associated with higher amounts of body fat, which could increase the risk of developing cardiovascular disease (CVD). A significant factor associated with CVD is metabolic syndrome (MetS), and MetS prevalence differs by race/ethnicity. The purpose of this study was to compare the prevalence and predictors of ORCs by race/ethnicity among adults (>18) with MetS. Methods This was a retrospective, cross-sectional study using data from the 1999-2014 National Health and Nutrition Examination Survey (NHANES). A chi-square test was performed to determine differences in ORC prevalence between non-Hispanic White (NHW), non-Hispanic Black (NHB), and Hispanic participants with MetS. A multivariate logistic regression was used to evaluate predictors (race, sex, income, insurance, education, marital status, and smoking status) of ORC among adults with MetS. Results Of the 1,554 adults, the prevalence of ORC was 30.6% among NHWs, 51.3% in NHBs, and 54.1% in Hispanics (p = <0.001). Females were 6.27 times more likely to have an ORC compared to males (95% CI = 4.95-14.11). Compared to NHWs, NHBs were 2.1 times more likely to have an ORC (95% CI = 1.40-3.38); and Hispanics were 2.5 times more likely (95% CI = 1.39-4.77). For every 1-year unit increase in age, the odds of ORC increased by 3% (95% CI = 1.00-1.05). Conclusions Among NHANES participants with MetS, the prevalence of ORCs was significantly higher in NHBs and Hispanics, females, and older adults with MetS. Future studies, by race/ethnicity, are warranted on mortality risk of persons with MetS and ORC.